Nutrient uptake and yield of common bean fertilized with poultry litters and mineral nutrients Crescimento e absorção de nutrientes pelo feijoeiro adubado com cama de aves e fertilizantes minerais - Lourenco K.S.* (2013)
Common bean is traditionally grown on small farms in Brazil, where animal wastes are often used as soil fertilizer. Since this is a short-cycle species, nutrients must be available soon after seed germination, which is not always the case when supplied in the form of organic fertilizers. This study was carried out to evaluate the efficiency of different poultry litters in comparison with mineral fertilizers to increase dry matter yield and nutrient release to beans. The experiment was conducted in 2010, in a greenhouse, with Oxisol samples containing16 g kg-1 of organic matter, 1.9 and 84 mg dm-3 of P and K, respectively, and with a pH of 6.0. A randomized complete block design was used with 10 treatments and five replications. The experimental units consisted of 14 dm3 of soil (dry base) in plastic pots, where five seedlings (cultivar BRS Requinte) were grown for 60 days. Treatments consisted of five poultry litters on the materials maize straw, sugar cane bagasse, native grass straw, sand and pine needles, respectively, and four mineral nutrient combinations (NPK, NP, PK, and NK), plus one control without any fertilizer. Mineral fertilizers containing P induced higher dry matter yield of shoot and roots of bean than the poultry litters, due to the release of higher amounts of available N and P. Of the animal wastes, the poultry litter with sand substrate was the most efficient to promote bean yield. Plants fertilized with poultry litters accumulated, on average 58.6 and 59.0 %, respectively, of the N and P accumulated in plants treated with mineral fertilizers containing N and P. The N and K recovery rate by plants was always higher for nutrients applied in mineral than organic forms. Poultry litters may be used as soil fertilizer of common beans provided they are supplemented with mineral fertilizers containing N and P.